Research on the opportunities and challenges brought by e-sports to Chinese sports - Fang, X. (Frontiers in Sport Research, 2019)
Sports is an important symbol of human progress and social development. The sports industry plays a very important role in China's economic development and is an important reflection of China's comprehensive national strength and social civilization. The "General Fitness Regulations" promulgated in 2009 stated that the state supports, encourages and promotes the development of sports consumption and the sports industry that meet the people's living standards. As a sports project, e-sports is being carried out in full swing in recent years, which has further promoted the transformation and upgrading of sports and brought huge economic and social benefits. This research studies the development of e-sports in China, hoping that it will enable people to have a deeper understanding of e-sports, seize the opportunities to meet the challenges, and further develop China's sports, and make relevant suggestions.